2021
DOI: 10.3390/biom11050677
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the Molecular Mechanisms Underlying the Protective Effect of Lactate on the High-Pressure Resistance of Listeria monocytogenes

Abstract: Formulations with lactate as an antimicrobial and high-pressure processing (HPP) as a lethal treatment are combined strategies used to control L. monocytogenes in cooked meat products. Previous studies have shown that when HPP is applied in products with lactate, the inactivation of L. monocytogenes is lower than that without lactate. The purpose of the present work was to identify the molecular mechanisms underlying the piezo-protection effect of lactate. Two L. monocytogenes strains (CTC1034 and EGDe) were i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…The effect of preservatives (additives, such as organic acids) on HPP microbial inactivation can vary: some studies reported enhanced inactivation of Salmonella in a raw meat matrix when lactic acid was added (Serra‐Castello et al., 2019), while when used as a salt (i.e. lactate) they show a dose‐dependent piezo‐protective effect on L. monocytogenes in laboratory media (Serra‐Castello et al., 2021a) and in different types of meat products (Marcos et al., 2008b; Lerasle et al., 2014; Stollewerk et al., 2014; Serra‐Castello et al., 2021b).…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of preservatives (additives, such as organic acids) on HPP microbial inactivation can vary: some studies reported enhanced inactivation of Salmonella in a raw meat matrix when lactic acid was added (Serra‐Castello et al., 2019), while when used as a salt (i.e. lactate) they show a dose‐dependent piezo‐protective effect on L. monocytogenes in laboratory media (Serra‐Castello et al., 2021a) and in different types of meat products (Marcos et al., 2008b; Lerasle et al., 2014; Stollewerk et al., 2014; Serra‐Castello et al., 2021b).…”
Section: Assessmentmentioning
confidence: 99%
“…2.8% (Serra‐Castello et al., 2021b). Though the effect might be partially related to the a w lowering effects of lactate, other mechanisms might be involved as the protection has been found even without changing the physico‐chemical characteristics of the product (Marcos et al., 2008a; Lerasle et al., 2014; Serra‐Castello et al., 2021a,b). Other organic acids in the form of salt, that can be used in RTE foods include acetate/diacetate (alone or in combination with lactate).…”
Section: Assessmentmentioning
confidence: 99%